2013
DOI: 10.4322/rca.2013.054
|View full text |Cite
|
Sign up to set email alerts
|

Toposequences of soils developed on basaltic rocks: physicochemical attributes

Abstract: Soils are formed in a structural continuity of layers along a toposequence. The objective of this study was to characterize the chemical and physical properties of soils in two topossequences derived from basaltic rocks in the state of Parana, with different slopes, aiming to identify the relationships between their attributes, relief, and parent material. We studied two toposequences, with differentiated reliefs, developed on parent material consisting of vesicular and aphanitic basaltic rocks. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…4, 5). The MWD values of our study are within the expected range, as observed by other authors studying soils weathered from basalt in Paraná ( Barbosa et al 2015;Gonçalves et al 2013). These soils have a good resistance to hydric erosion (Reichert et al 2009) and the increment in MWD caused by chicken manure can intensify this characteristic, once some studies suggest that aggregates bigger than 2 mm are less susceptible to be transported by water (Calegari et al 2006;Xiao et al 2017).…”
Section: Resultssupporting
confidence: 89%
“…4, 5). The MWD values of our study are within the expected range, as observed by other authors studying soils weathered from basalt in Paraná ( Barbosa et al 2015;Gonçalves et al 2013). These soils have a good resistance to hydric erosion (Reichert et al 2009) and the increment in MWD caused by chicken manure can intensify this characteristic, once some studies suggest that aggregates bigger than 2 mm are less susceptible to be transported by water (Calegari et al 2006;Xiao et al 2017).…”
Section: Resultssupporting
confidence: 89%
“…Gambiza (2001) reported that the patchy distribution of the soil types and topographic features modify plant-available moisture and available nutrients, thereby influencing plant structure. Soil nutrients can be influenced by physicochemical properties of the geological substrate and mostly by undulating relief downstream the soils (Gonc¸alves et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…), resources availability, and species competitive abilities would likely codetermine species structural and dominance patterns (Mensah, Salako, Assogbadjo, & Gle`le`Kakaı¨, 2018;Zhang, Chen, Liu, & Pei, 2016). For example, environmental factors such as soil physical properties and slope were pointed out as potential drivers of vegetation structure and distribution (Gonc¸alves, Filho, Vendrame, & Telles, 2013). Therefore topography-and relief-related conditions (Asse´de´, Azihou, Adomou, Oumorou, & Sinsin, 2015) would also influence A. africana population's structure.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the agricultural soils elsewhere, the soils of the present study site are developed on diverse parent materials and support different arable crops. In addition, comparing the potential of soil developed on diverse parent materials for agricultural productivity had mixed results as reported by (Abam and Orji 2019; Donatus et al 2018;Corbett 2006;Gonçalves et al 2013;Graham et al 2017). However, Afu et al (2021 and Ofem et al (2020) have reported limestone, shale, and basaltic-derived soils to be suitable for agricultural production.…”
Section: Discussionmentioning
confidence: 94%